Conceptual design of PrandtlPlane civil transport aircraft. (August 2020) - Frediani, A; Cipolla, Vittorio; Salem, K Abu; Binante, V; Scardaoni, M Picchi
According to aircraft manufacturers and several air transportation players, the main challenge the civil aviation will have to deal with in the future is to provide a sustainable growth strategy, in order to face the growing demand of air traffic all over the world. The sustainability requirements are related to air pollution, noise impact, airport congestion, competitiveness of the air transportation systems in terms of travel time and passengers' comfort. Among the possible ways to allow a sustainable growth of the air transportation systems, disruptive aircraft configurations have been object of study for several years, in order to demonstrate that the improvement of aircraft performance can enable the envisaged growth. This paper presents the study of a possible novel configuration called "PrandtlPlane, " having a box-wing layout derived from Prandtl's "Best Wing System" concept. The paper deals with the definition of top level requirements and faces the conceptual study of the overall configuration, focusing on fuselage sizing as well as on the aerodynamic design of the box-wing system. This latter is designed through an optimization-driven strategy, carried out by means of a low-fidelity aerodynamic tool, which simulates the flow condition in the subsonic range and introduces corrections to take the transonic effects into account. Design procedures and tools are presented, showing preliminary results related to a PrandtlPlane compliant with ICAO Aerodrome Reference Code "C" standard, such as Airbus A320 and Boeing 737, whose wingspan is limited to 36 m. Activities and results here shown are part of the first phase of the research project "PARSIFAL" (Prandtlplane ARchitecture for the Sustainable Improvement of Future AirpLanes), funded by the European Commission under the Horizon 2020 Program, which aims to demonstrate that the PrandtlPlane configuration can improve aircraft payload capability, keeping their dimensions compatible with present airport infrastructures.